Revealing the morphology and function of the cochlea and middle ear with optical coherence tomography - Burwood, George W. S.; Fridberger, Anders; Wang, Ruikang K.; Nuttall, Alfred L. (Quantitative Imaging in Medicine and Surgery, 2019)
Optical coherence tomography (OCT) has revolutionized physiological studies of the hearing organ, the vibration and morphology of which can now be measured without opening the surrounding bone. In this review, we provide an overview of OCT as used in the otological research, describing advances and different techniques in vibrometry, angiography, and structural imaging.